Comparative Analysis of Ratoon-Competent and Ratoon-Deficient Sugarcane by Hormonal and Transcriptome Profiling - Liping Zhao; Maoyong Ran; Jing Zhang; Peifang Zhao; Fenggang Zan; Jun Zhao; Wei Qin; Qibin Wu; Jiayong Liu; Xinlong Liu (Agronomy, 2025)
The ratooning capacity of sugarcane cultivars represents a crucial agronomic trait that significantly influences the sustainability of crop yields. This study elucidates the physiological and molecular mechanisms underlying the sugarcane ratooning ability observed in ratoon-competent GuiTang 29 (GT29) and ratoon-deficient Badila cultivars following stem excision. Through integrated hormonal profiling and transcriptome analysis, we identified significant differences in hormone levels and gene expression patterns. The quantification of 15 endogenous hormones via HPLC revealed marked reductions in zeatin (ZA) and zeatin riboside (ZR) in both cultivars. Additionally, GT29 exhibited notable reductions in gibberellins (GA3 and GA5) and strigolactone (5-DS) post-stem-excision, while Badila displayed stable or distinct hormonal changes. Additionally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses indicated that hormone signal transduction, MAPK signaling pathways, phenylpropanoid biosynthesis, flavonoid biosynthesis, and other metabolic pathways were significantly enriched in both GT29 and Badila, with a particularly higher enrichment of plant hormone signal transduction in GT29. Furthermore, several differentially expressed genes (DEGs) had different expression patterns between GT29 and Badila, including the cytokinin receptor B-ARR and transcription factor A-ARR, gibberellin pathway components GID1 and DELLA, and AUX/IAA and SAUR in the auxin pathway. The real-time quantitative PCR (qRT-PCR) validation of 12 DEGs corroborated the RNA-seq data, further supporting the reliability of the transcriptomic analysis. This study delineates a clear molecular framework distinguishing ratoon competence, offers novel insights into the molecular basis of perennial regeneration and provides reliable candidate genes for functional marker development in sugarcane breeding.